Telbivudine is associated with improvement of renal function in patients transplanted for HBV liver disease. Issue 7 (11th November 2014) - Cholongitas, E.; Vasiliadis, T.; Goulis, I.; Fouzas, I.; Antoniadis, N.; Papanikolaou, V.; Akriviadis, E.
Summary Recent studies showed that telbivudine in patients with hepatitis B virus (HBV) infection improved their glomerular filtration rate (GFR), but data regarding its impact on renal function in liver transplant (LT) recipients are very limited. We evaluated 17 consecutive recipients who received at baseline nucleos(t)ide analogue(s) (NAs) other than telbivudine for 12 months, and then they were switched to telbivudine prophylaxis for another 12 months. In each patient, laboratory data including evaluation of GFR (using MDRD and CKD‐EPI) were prospectively recorded. The changes in GFR (ΔGFR) between baseline and after 12 months (1st period) and between telbivudine initiation and 24 months (2nd period) were evaluated. All patients remained serum HBsAg and HBV‐DNA negative. GFR‐MDRD at baseline, 12 months and 24 months were 72 ± 18, 67.8 ± 16 and 70.3 ± 12mL/min, respectively, (P = 0.025 for comparison between 12 months and 24 months). ΔGFR at the 1st period was significantly lower, compared with ΔGFR at the 2nd period [mean ΔGFR‐MDRD: −4.2 (range: −24–9) vs 2.5 (range: −7–22) mL/min, P = 0.013; mean ΔGFR‐CKD‐EPI: −4.2 (range: −19–10) vs 4.0 (range: −7–23) mL/min, P = 0.004], although the serum levels of calcineurin inhibitors were similar between the two periods. A second group of recipients (n = 17) who remained under the same nontelbivudine NA(s) for 24 months had a decline in the mean eGFR during the total follow‐up period. In conclusion, we showed that telbivudine administration in LT recipients for HBV cirrhosis was effective and it was associated with significant improvement in renal function, but this remains to be confirmed in larger well‐designed studies.